Recent advances in membrane aerated biofilm reactors. Issue 7 (3rd April 2021) - Lu, Duowei; Bai, Hao; Kong, Fangong; Liss, Steven N.; Liao, Baoqiang
Abstract: Membrane aerated biofilm bioreactors (MABRs), a relatively new innovation in biological wastewater treatment technology, have received much attention in recent years. In the past two decades, the emphasis has focused on exploring and verifying the advantages of MABRs for wastewater treatment through experimental and modeling studies. In-depth fundamental understanding of MABRs and their design have been achieved. Pilot-scale studies and full-scale applications of MABRs have been reported. MABR technology has been successfully applied for high strength industrial wastewater treatment and refractory pollutant removal, simultaneous removal of chemical oxygen demand (COD) and nitrogen (N) in municipal wastewater treatment, and retrofitting of existing activated sludge plants. The advantages of MABRs include high oxygen transfer efficiency, effective COD/N removal, improved energy efficiency, and the relative ease in scale-up. The importance of biofilm thickness control, potential for new applications, and design of low-cost and high efficient membrane materials and modules call for further studies to advance MABR technology. Recent advances in physico-chemical properties of membranes, factors affecting MABR performance, microbial communities, and modeling in MABRs are systematically reviewed. A number of important challenges and unexplored opportunities remain pointing in the direction of future research and development needs. Highlights: MABR technology has reached to pilot-scale and full-scale applications for wastewater treatment. Significant processes in fundamental understanding of process design and applications of MABR has achieved. Process, microbiological, and membrane factors affecting MABR performance are reviewed and discussed. Biofilm thickness control, new membrane materials and module design, and new applications of MABRs call for further studies. Abstract : UF0001